2002
DOI: 10.1073/pnas.042688699
|View full text |Cite
|
Sign up to set email alerts
|

A comparative radiation hybrid map of bovine chromosome 18 and homologous chromosomes in human and mice

Abstract: A comprehensive radiation hybrid (RH) map and a high resolution comparative map of Bos taurus (BTA) chromosome 18 were constructed, composed of 103 markers and 76 markers, respectively, by using a cattle-hamster somatic hybrid cell panel and a 5,000 rad whole-genome radiation hybrid (WGRH) panel. These maps include 65 new assignments (56 genes, 3 expressed-sequence tags, 6 microsatellites) and integrate 38 markers from the first generation WGRH5,000 map of BTA18. Fifty-nine assignments of coding sequences were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…The QTL effect for udder depth at position 30 cM could be due to the correlation of this trait with SCS (LUND et al, 1994). Several studies (e.g., GOLDAMMER et al, 2002;BRUNNER et al, 2003) have reported that the telomeric region of BTA18 exhibits high similarity to the HSA19q region in humans, that contains several gene families with effect on the immune system such as the SIGLEC-(sialic acid binding Ig-like lectin), the KIR-(killer cell immunoglobulin-like receptor) and the LILR (leukocyte immunoglobulin-like receptor) gene clusters. For the peak at 34 cM, there are a lot of these above mentioned genes possibly suitable as candidates for further studies.…”
Section: Resultsmentioning
confidence: 99%
“…The QTL effect for udder depth at position 30 cM could be due to the correlation of this trait with SCS (LUND et al, 1994). Several studies (e.g., GOLDAMMER et al, 2002;BRUNNER et al, 2003) have reported that the telomeric region of BTA18 exhibits high similarity to the HSA19q region in humans, that contains several gene families with effect on the immune system such as the SIGLEC-(sialic acid binding Ig-like lectin), the KIR-(killer cell immunoglobulin-like receptor) and the LILR (leukocyte immunoglobulin-like receptor) gene clusters. For the peak at 34 cM, there are a lot of these above mentioned genes possibly suitable as candidates for further studies.…”
Section: Resultsmentioning
confidence: 99%
“…BTA18 has the largest number of mapped markers (n = 121), whereas BTA28 has the fewest (n = 23). Relative differences in marker distribution are due in part to targeting of specific chromosomes for high-density mapping (e.g., BTA18; Goldammer et al 2002) as well as chromosome size. The average chromosome length is 397 cR 5000 , ranging from 563 cR for BTA16 to 150 cR for BTA20 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…PCR typing of TLR9 was performed in a cattle-mouse somatic-hybrid cell (SHC) panel (55), and in a cattle-hamster 5,000-rad wholegenome radiation hybrid panel WGRH 5000 (54), essentially as described previously (18). The WGRH typing experiment was performed twice, and data were scored independently.…”
Section: Methodsmentioning
confidence: 99%